Fotografie in Oost-Vlaanderen. - Gysegem, M. van; Huys, P. (Oost-Vlaanderen : Provinciebestuur, 1992)
Boon, Jo ; Bottequin, Jean-Marie ; Braeckman, Dirk ; Buyle, Charles ; Claerhout, Eric ; Claus, Filip ; Colruyt, Lieve ; Dauw, Leslie ; De Keyzer, Carl ; De Malsche, Pol ; De Mulder, Walter ; De Munter, Longinus ; Deruyter, Jan ; De Smedt, Raf ; De Spiegelaere, Patrick ; De Vos, Johan ; Geirlandt, Toni ; Heirbaut, Karel ; Heirman, Rony ; Hendryckx, Michiel ; Hoflack, Mark ; Kessels, Willy ; Leirens, Charles ; Libens, Daniël ; Marchal, Guy ; Sonck, Jacques ; Uytterhaegen, C&arl ; Van Beeck, Martien ; Van den Abeele, Paul ; Van derhegghen, Aloïs ; Stricht, Colette Vander ; Vandevelde, Juul ; Van Roy, Marc ; Verspeeten, Armand ; Wauters, Jan
boek